PENGARUH ETOS KERJA, KEPEMIMPINAN DAN KOMITMEN KERJA TERHADAP KINERJA PEGAWAI BAGIAN PENGADAAN BARANG/JASA SEKRETARIAT DAERAH KABUPATEN PASURUAN - Timbul Hariono; Sundjoto, Sundjoto; Sri Rahayu (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to analyze the influence of work ethic, leadership, and work commitment on employee performance, both simultaneously and partially, as well as to determine which variable has the most dominant influence. The subjects of the research were all administrative and financial employees in the Procurement of Goods/Services Division of the Regional Secretariat of Pasuruan Regency, totaling 31 individuals. Due to the relatively small population size, a census method was used, in which the entire population served as the sample. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results show that simultaneously, work ethic, leadership, and work commitment have a significant influence on employee performance. Partially, each of these variables also has a significant effect on performance. Among them, work ethic is found to be the most dominant factor affecting employee performance. These findings highlight the importance of fostering a strong and professional work culture to enhance organizational performance.